Absorption Spectroscopy for Antibacterial Agents Selectivity and Their Toxicity to the Host - Dr Sunil Bhatt (Genius Journals, 2021)
The use of inorganic compounds in medical practise dates back to ancient times. In spite of this, significant progress has been made in this area through the completion of species and the articulation of chelating agents. These chelating agents must, by definition, contain two or more electron donor groups that are in a position to co-ordinate with a metal ion in order to form one or more stable ring structures with five or six members each. There is compelling evidence to suggest that chelation is the fundamental mechanism behind the therapeutic effects of a large number of natural and synthesised medicinal medicines. Because it is not possible to infuse metals directly. Because they do not target specific bacteria and are hazardous to the host, they are able to enter the bloodstream and operate as antibacterial agents. Additionally, in order to carry out their function, soluble metal ions such as iron are able to pass through the membranes that surround bacterial cells. Van Bohring discovered that diphtheria may be healed by a serum that is made by injecting bacteria into a healthy animal and then collecting serum from the immunised animal after the caused sickness has passed. Biotherapy may take many forms, including vaccination and serum treatment, and its early, remarkable achievements inspired the optimism that all contagious illnesses could one day be prevented or cured using these methods. Prophylactic vaccination, also known as active immunisation, has been demonstrated to be very successful in human therapy only against smallpox, typhoid fever, and rabies. The only other disease that prophylactic vaccination has been shown to be beneficial against is scarlet fever. Serum treatment has only been shown to be effective for a select few human diseases, such as diphtheria bacillary desentry. Snake bites are one of these disorders. Biotherapy has only found limited use due to the large number of known microorganisms that may cause disease in humans
Keywords: Absorption; spectroscopy; antibacterial; agents